Studying the Structural Significance of Galectin Design by Playing a Modular Puzzle: Homodimer Generation from Human Tandem-Repeat-Type (Heterodimeric) Galectin-8 by Domain Shuffling - Anna-Kristin Ludwig; Malwina Michalak; Nadya Shilova; Sabine André; Herbert Kaltner; Nicolai V. Bovin; Jürgen Kopitz; Hans-Joachim Gabius (Molecules, 2017)
Tissue lectins are emerging (patho)physiological effectors with broad significance. The capacity of adhesion/growth-regulatory galectins to form functional complexes with distinct cellular glycoconjugates is based on molecular selection of matching partners. Engineering of variants by changing the topological display of carbohydrate recognition domains (CRDs) provides tools to understand the inherent specificity of the functional pairing. We here illustrate its practical implementation in the case of human tandem-repeat-type galectin-8 (Gal-8). It is termed Gal-8 (NC) due to presence of two different CRDs at the N- and C-terminal positions. Gal-8N exhibits exceptionally high affinity for 3′-sialylated/sulfated β-galactosides. This protein is turned into a new homodimer, i.e., Gal-8 (NN), by engineering. The product maintained activity for lactose-inhibitable binding of glycans and glycoproteins. Preferential association with 3′-sialylated/sulfated (and 6-sulfated) β-galactosides was seen by glycan-array analysis when compared to the wild-type protein, which also strongly bound to ABH-type epitopes. Agglutination of erythrocytes documented functional bivalency. This result substantiates the potential for comparative functional studies between the variant and natural Gal-8 (NC)/Gal-8N.